Im Nebel Der junge Georg Lukács und Wien - Kókai, Károly (2002)
The relationship between the intellectual development of the young Georg Lukacs and the culture of Vienna around the turn of the century was investigated in the research project: Georg Lukacs and Vienna. Because of this the main point of interest was to investigate aspects of his work which stand in relation to Vienna around 1900. First of all the results of previous research about the theme 'Lukacs and Vienna' were held onto. After this, the methodical procedure from cultural studies about the turn of the century, which are treated as the standard works in this field, we re sketched out and the methods for contemporary works were laid down. The relevant biographical facts were laid out in two chapters about his life and his education - with special attention being paid to the question of his introduction to the problems of contemporary Austrian philosophy. The effect of Rudolf Kassner on Lukacs thoughts around 1910 seems to be very important. Lukacs' literature critical texts on modern Austrian drama especially the literature of Arthur Schnitzler and Richard Beer-Hofmann play a central role. The theories, which are developed in these texts, were made more precise in a discussion with Mihaly Babits as well as in the text: Aesthetic Culture. Following this Lukacs' aesthetical Heidelberg writings, which are relevant to the investigation of this project, were analyzed. The insight into the theories, which show up in Lukacs' texts, which was won in the research project through the aforementioned writings was then deepened with consideration to the Jewish Question as well as with an analysis of the concepts of liberalism, culture, and the Modern. At the same time Lukacs' activities were placed in the context of Central Europe. In addition the question was answered: what meaning did the relationship between Lukacs and Vienna have for his later development. The result of the project is that insight into Georg Lukacs must be viewed in the context of modernity and Central Europe, in order to understand his activity and, in a very concrete way, in order to understand his individual texts. If one doesn't take his contradictory relationship to Vienna around 1900 and to the Modern and Central Europe into account he remains a confused solitary person. Afurther and perhaps even more important result is: When one places Lukacs in the relation of these aforementioned intellectual-historical appearances, these appearances themselves win on dimensions, which first make their understanding possible.